Spectrophotometric Determination of Zolmitriptan in Pharmaceutical Dosage Forms - Sankar, D. Gowri; Babu, A. Nagesh; Rajeswari, A.; Krishna, M. Vamsi; Devi, K. Vanisha (Asian Journal of Chemistry, 2010)
A new UV spectrophotometric method has been developed for the quantitative estimation of zolmitriptan in pure form as well as in pharmaceutical formulations. The drug exhibits absorption maximum at 226 nm in methanol and obeys Beer's law in the concentration range of 1-6 μg/mL. The method was extended to pharmaceutical preparations and there is no interference from any common pharmaceutical additives.